Impact of International Atomic Energy Agency support to the development of nuclear cardiology in low-and-middle-income countries: Case of Latin America and the Caribbean (2019)
Cardiovascular diseases (CVDs) are the leading cause of death in Latin America and the Caribbean (LAC) region as well as worldwide. Lifestyle, nutritional habits and the upsurge of obesity have contributed to the increase in the prevalence of CVDs in the region. The role of nuclear cardiology in the management of patients with CVDs is well established. Particularly, myocardial perfusion imaging is widely used in LAC countries and has been increasingly integrated into the healthcare systems in the region for the diagnosis of coronary artery disease, risk stratification and to guide patient management. In its role to support countries around the world to address their health needs through the peaceful applications of nuclear techniques, the International Atomic Energy Agency (IAEA) has provided assistance to the LAC region for the establishment and strengthening of the nuclear cardiology practice. To that extent, the IAEA provides support in building capacities of multidisciplinary teams of professionals, the provision of medical equipment and the promotion of communication and exchange of knowledge among the different stakeholders. In addition, the IAEA encourages the participation of nuclear medicine centers in international multi-center research studies. In this paper, we present some of the projects through which the IAEA has supported the LAC region, including regional technical cooperation projects and coordinated research projects related to cardiology within the current multimodality approach to cardiac imaging. © 2019, The Author(s).